2019
DOI: 10.1021/acs.bioconjchem.8b00849
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Structure–Activity Relationship of the Pentaglutamic Acid Sequence of Minigastrin with Cholecystokinin Receptor Subtype 2

Abstract: Derivatized minigastrin analogues make up a promising class of candidates for targeting cholecystokinin receptor subtype 2 (CCK2R), which is overexpressed on cancer cells of various neuroendocrine tumors. The pentaglutamic acid sequence of minigastrin influences its biological properties. In particular, it plays a crucial role in the kidney reuptake mechanism. However, the importance of the binding affinity and interaction of this region with the receptor on a molecular level remains unclear. To elucidate its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…Both [ 225 Ac]Ac-PP-F11N and [ 177 Lu]Lu-PP-F11N showed high internalization efficiency in vitro. Ritler et al reported [ 177 Lu]Lu-PP-F11N internalization rate of 50.2% ± 8.9 after 2 h incubation in CCKBR positive cells recently [ 16 ], which is similar to the internalization rate of [ 225 Ac]Ac-PP-F11N (45.9% ± 1.6) in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Both [ 225 Ac]Ac-PP-F11N and [ 177 Lu]Lu-PP-F11N showed high internalization efficiency in vitro. Ritler et al reported [ 177 Lu]Lu-PP-F11N internalization rate of 50.2% ± 8.9 after 2 h incubation in CCKBR positive cells recently [ 16 ], which is similar to the internalization rate of [ 225 Ac]Ac-PP-F11N (45.9% ± 1.6) in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The evaluation of the different radiolabeled minigastrin derivatives differing in both, the Cterminal peptide binding moiety and the structural characteristics of the linker, revealed that the compounds with six D-glutamic acid residues within the amino acid chain belong to the most promising substances with an reasonable balance of tumor uptake and decreased kidney reabsorption (11,12,16). The pronounced hydrophilicity of such compounds is most likely the reason for the fast renal excretion and shorter blood half-life of 177 Lu-PP-F11N in comparison to…”
Section: Discussionmentioning
confidence: 99%
“…jnm.snmjournals.org Downloaded from effect. Another approach to reduce nephrotoxicity is to modify the compound itself: Amino acid chains with more than 5 glutamic acids in their sequence play an important role in the kidney reuptake mechanism and may reduce kidney uptake (10,11). Such an approach was implemented by several groups and resulted in the development of a library of improved radiolabeled minigastrin analogues (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 447 residues in the full CCK2R sequence, the following are susceptible to 1 O 2 oxidation: 10 Met residues-Met1, Met67, Met73, Met108, Met117, Met134, Met186, Met234, Met334, and Met393; 15 Cys residues-Cys22, Cys39, Cys107, Cys127, Cys157, Cys205, Cys279, Cys293, Cys345, Cys384, Cys391, Cys401, Cys405, Cys408, and Cys409; 6 His residues-His170, His207, His274, His364, His376, and His394; 6 Trp residues-Trp165, Trp179, Trp209, Trp218, Trp346, and Trp355; and 12 Tyr residues-Tyr61, Tyr132, Tyr153, Tyr189, Tyr192, Tyr238, Tyr246, Tyr294, Tyr350, Tyr380, Tyr390, Tyr438, Tyr61, Tyr189, Tyr192, and Tyr350 ( Figure A1 in Appendix A). The CCK2R residues that have been found to be essential for CCK binding (as determined by site-directed mutagenesis and photoaffinity labeling) are as follows: Arg57, Tyr61, Thr111, Thr119, Phe120, Phe122, Tyr189, Tyr192, Thr193, His207, Phe227, Phe342, Trp346, Val349, Tyr350, Asn353, Arg356, and His376 [65][66][67][68][69][70][71]. The overlapping residues in CCK2R are Tyr61, Tyr189, Tyr192, His207, Trp346, Tyr350, and His376.…”
Section: Discussionmentioning
confidence: 99%